2022
DOI: 10.3390/diagnostics12122901
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic AI and Cardiac Diseases

Abstract: (1) Background: The purpose of this study is to review and highlight recent advances in diagnostic uses of artificial intelligence (AI) for cardiac diseases, in order to emphasize expected benefits to both patients and healthcare specialists; (2) Methods: We focused on four key search terms (Cardiac Disease, diagnosis, artificial intelligence, machine learning) across three different databases (Pubmed, European Heart Journal, Science Direct) between 2017–2022 in order to reach relatively more recent developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…One potential area of future development is engineering in medical AI and medicine; there will probably be discussion in the future about physicians with exhaustive knowledge of medical AI. For significant technological progress and innovation, close collaborations between healthcare engineering systems and physicians are needed [ 250 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential area of future development is engineering in medical AI and medicine; there will probably be discussion in the future about physicians with exhaustive knowledge of medical AI. For significant technological progress and innovation, close collaborations between healthcare engineering systems and physicians are needed [ 250 ].…”
Section: Discussionmentioning
confidence: 99%
“…What can be done about patients’ data privacy and who should be trained to protect it? How can we prevent doctors’ judgmental standards from falling due to reliance on AI for diagnosis, which may become a serious problem in a few generations [ 250 ]? For correct and complete implementation, this side of AI must be addressed, and for the moment, it is one of the most sensitive issues.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Arti cial Intelligence (AI) and deep learning technologies have revolutionized image analysis and predictive modelling in healthcare 4 . Recent study has indicated that chest radiography can provide information not only traditional diagnosis tool but on cardiac function and biomarker of ageing [5][6][7][8] . In our previous study, physical characteristics were extracted from chest radiography to develop height and weight predictive model that assessed the nutritional status of older bedridden adults 9 .…”
Section: Introductionmentioning
confidence: 99%